A framework for the impact analysis on earthquakes and tsunamis on seaport operations by using evidential reasoning. Issue 3 (3rd July 2021) - Salleh, Nurul Haqimin Mohd; Alias, Siti Atikah Md; Ruslan, Siti Marsila Mhd
ABSTRACT: In terms of global transport issues, the port industry provides a major advantage by linking countries through seaborne trade. Nonetheless, natural hazards often threaten the profitability of seaport operations. Since most ports are situated in coastal areas, they are highly vulnerable to earthquakes and tsunamis. Earthquakes and tsunamis phenomena have been critically addressed at the operational planning stage in the maritime transport sector, where the disruption management department considers these phenomena as the major events that can lead to operation disruption. A new framework to study the destruction of earthquakes and tsunamis during seaport operations is established in this paper. For modeling the disruption analysis, a blend of various decision-making approaches such as Analytic Hierarchy Process (AHP) and Evidential Reasoning (ER), is used to model the disturbance analysis. Firstly, by using the AHP process, the disruption of earthquakes and tsunamis in seaport operations is defined and prioritized. Secondly, the disruption stages are assessed and synthesized by using the ER method. Penang Port is chosen as a case study to illustrate the applicability of the research model. This analysis model is capable of assisting seaport operators to perform self-assessment of earthquakes and tsunamis to improve the operational sustainability in a seaport.